MEM752: Facilities Management - Building & Infrastructure - UiTM, College of Engineering (2023)
The scope includes the management of facilities in building environment and infrastructure, the responsibility of facilities manager, asset management, maintenance, evaluation, and sustainable practices in facilities management so as to provide quality environment.